Negotiating space : the evolution of the Egyptian street, 2000-2011 - Soudias, Dimitris (Cairo Papers in Social Science, 2014)
This monograph offers a diachronic analysis of the development of street protests in Egypt that led to the downfall of Mubarak in 2011. It shows how the January 25 uprising was the culminating episode of negotiating power relations in a series of five consecutive contentious cycles since 2000. -- Provided by publisher.